2011
DOI: 10.1055/s-0031-1280802
|View full text |Cite
|
Sign up to set email alerts
|

Modified Lotus Petal Flap for Vulvo-Vaginal Reconstruction after Resection for Vulvar Cancer − A Single Institution Experience

Abstract: Introduction: Tumour of the vulva is an uncommon pathology that requires radical surgery with wide tumour excision associated with lymphadenectomy. The reconstruction after demolitive surgery is necessary, and the need of new flaps has led us to evaluate the feasibility and efficacy of the previously described lotus petal flap, a local subcutaneous pedicle rotation flap. However, the lotus petal flap has not yet come into wide use, moreover, in the literature there are still only few papers on this topic. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…However, because the blood supply of the tissue imported in the form of tunneled lotus flap remains uninterrupted, the risk of such a problem is reduced even in patients who were operated on more than once. The low complication rate in our hands, which is consistent with previous reports, 3,4,6,8,14,15 provides further evidence that the procedure is safe and easy to perform, even in the setting of recurrent disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, because the blood supply of the tissue imported in the form of tunneled lotus flap remains uninterrupted, the risk of such a problem is reduced even in patients who were operated on more than once. The low complication rate in our hands, which is consistent with previous reports, 3,4,6,8,14,15 provides further evidence that the procedure is safe and easy to perform, even in the setting of recurrent disease.…”
Section: Discussionsupporting
confidence: 91%
“…14 In addition, in this series of 22 tunneled lotus petal flaps, the complication rate was 9%, similar to our previous published data. 6 The tunneled lotus petal flap has been introduced in our practice at the beginning of 2010 and, when applicable the flap lies without tension, has a better anatomic definition, with excellent cosmetic and functional long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Yii et al [14] were the first in 1996 to report on reconstruction using the LP flap. All but three of these studies are case series [14][15][16][17][18][19][20][21][22][23][24][25][26]. Only Negosanti et al [27], Confalonieri et al [18] and Thiele et al [28] reported a case control study in which a reconstruction with LP flaps was compared with other flaps.…”
Section: Lp Reconstructionmentioning
confidence: 99%
“…About half of the studies (56.3%) were small studies (<20 patients), the largest was that of Confalonieri et al which included 106 patients [14,18,[20][21][22]24,[26][27][28]. In 62.5% of the studies, only females were included [14,15,[17][18][19]21,23,[25][26][27]. Mean age of the subjects varied between 50.3 years and 79 years [21,22].…”
Section: Lp Reconstructionmentioning
confidence: 99%
“…3,4 From 2007, we identified LPF as the most appropriate method of reconstruction after vulvoperineal surgery for both primary and recurrence vulvar malignancy.…”
mentioning
confidence: 99%